Introduction to Programming using Fortran 95/2003/2008 - Jorgensen, Ed; Open Textbook Library (Open Textbook Library, 2018)
Computers are everywhere in our daily lives. Between the desktop, laptop, phone, bank, and vehicle, it is difficult to completely get away from computers. It only makes sense to learn a little about how a computer really works.This text provides an introduction to programming and problem solving using the Fortran 95/2003/2008 programming language. This introduction is geared for non-computer science majors. The primary focus is on an introduction to problem solving and algorithm development. As such, many details of the Fortran 95/2003/2008 language are omitted.
1 Introduction -- 2 Computer Organization -- 3 Getting Started -- 4 Fortran 95/2003/2008 - Basic Elements -- 5 Expressions -- 6 Simple Input and Output -- 7 Program Development -- 8 Selection Statements -- 9 Looping -- 10 Formatted Input/Output -- 11 Characters and Strings -- 12 File Operations -- 13 Single Dimension Arrays -- 14 Multidimensional Arrays -- 15 Subprograms -- 16 Derived Data Types -- 17 Modules -- 18 Recursion -- 19 Character String / Numeric Conversions -- 20 System Services -- 21 Appendix A - ASCII Table -- 22 Appendix B - Start-Up Instructions -- 23 Appendix C - Random Number Generation -- 24 Appendix D - Instrinsic Functions -- 25 Appendix E - Visualization with GNUplot -- 26 Appendix F - Quiz Question Answers -- 27 Appendix G - Fortran 95/2003/2008 Keywords
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks; Programming Languages -- Textbooks